Zirconia in Dental Implantology: A Review of the Literature with Recent Updates - Sami Aldhuwayhi (Bioengineering)
Zirconia dental implants have emerged as a transformative material in implantology, offering a biocompatible, esthetic, and durable alternative to traditional titanium implants. This comprehensive review explores the key properties of zirconia, including high fracture resistance, esthetic superiority, and low bacterial affinity. The ability of zirconia to integrate with bone through osseointegration, coupled with its resistance to plaque and inflammation, results in a product that is particularly suitable for patients with metal sensitivities or high esthetic demands. However, challenges such as brittleness and complex manufacturing processes persist. Advances in surface modification techniques and material optimization are poised to address these limitations, paving the way for broader applications. The purpose of this descriptive review was to emphasize the mechanical, antibacterial, osteointegration and survival rates of zirconia implants. This paper also summarizes findings from recent empirical studies, highlighting zirconia’s clinical performance, biological responses, and future potential as a mainstream implant material.